THE ROLE OF THE AT-TAQWA MAJELIS TAKLIM IN SHAPING SOCIAL INTERACTION PATTERNS AND COMMUNITY LIFE IN SIDOREJO, NORTH SUMATRA - Winda Kustiawan; Latifah Rahmawati; Sri Idah Wati Harahap; Raysa Finarik Rambe (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to explore the presence of community-based organizations and their role as beneficial instruments within society. Majelis taklim (Islamic study groups) are closely intertwined with the social fabric of the community, as every religious gathering (taklim) fosters social interaction either between individuals and congregants or among the congregants themselves. These social interactions frequently lead to broader social activities, both within the taklim community and the general public. However, social interaction and behavior are not always consistent among members of the wider society. It is recognized that when taklim serves as a space for learning and interaction, its participants tend to adopt a more refined and ethical way of life. This study employs a descriptive qualitative approach using action research methodology, aimed at generating a consistently positive understanding of the research object. Such an approach aligns well with the broader societal perception of Islamic education. The research seeks to identify the methods of Islamic preaching (da’wah) used in the sermons, analyze the content delivered, and examine how the audience (mad’u) applies these teachings in everyday life. The descriptive qualitative method is used to explain phenomena without altering the variables under investigation, relying primarily on discreet interviews for data collection. The primary goal of taklim is to deepen the understanding of its participants. Understanding, in this context, reflects the extent to which an individual comprehends a concept, situation, or fact that is clearly conveyed. This comprehension extends beyond verbal transmission to include mastery of the core issues or facts discussed. The existence of majelis taklim in this regard cannot be simply interpreted by the general public as a mere representation of religious ritual. Its integration into community life has become intrinsic to the participants. In this context, the enthusiasm and awareness of the congregants are evident through their active involvement in various religious activities.